2009
DOI: 10.1038/sj.bjc.6605182
|View full text |Cite
|
Sign up to set email alerts
|

Can cutaneous telangiectasiae as late normal-tissue injury predict cardiovascular disease in women receiving radiotherapy for breast cancer?

Abstract: Background: Overall, ∼5% of patients show late normal-tissue damage after radiotherapy with a smaller number having a risk of radiation-induced heart disease. Although the data are conflicting, large studies have shown increased risks of cardiovascular disease (CVD) for irradiated patients compared with non-irradiated ones, or for those treated to the left breast or chest wall compared with those treated to the right. Cutaneous telangiectasiae as late normal-tissue injury have so far only been reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…During or shortly after the course of breast cancer RT, a large portion of the patients will experience acute radiation dermatitis to some degree, varying from mild to brisk erythema with or without moist desquamation and occasionally ulceration of the skin [ 2 ]. There is accumulating clinical evidence that acute reactions are associated with the development of late toxicity: Lilla et al showed that telangiectasia are in fact late sequelae of moist desquamation and acute erythema is shown to be a risk factor for poor cosmetic outcome [ 3 5 ]. Though the skin is not a dose-limiting tissue, skin toxicity is associated with impairment of patients’ quality of life, causes pain and discomfort and limits activities [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…During or shortly after the course of breast cancer RT, a large portion of the patients will experience acute radiation dermatitis to some degree, varying from mild to brisk erythema with or without moist desquamation and occasionally ulceration of the skin [ 2 ]. There is accumulating clinical evidence that acute reactions are associated with the development of late toxicity: Lilla et al showed that telangiectasia are in fact late sequelae of moist desquamation and acute erythema is shown to be a risk factor for poor cosmetic outcome [ 3 5 ]. Though the skin is not a dose-limiting tissue, skin toxicity is associated with impairment of patients’ quality of life, causes pain and discomfort and limits activities [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…V 105% was chosen to specify the target volume receiving high doses. In addition, a conformity index (CI) was defined as CI 5 V ri / V PTV , where V ri is the volume encompassed by the reference isodose for the PTV (95% of the prescribed dose) and V PTV is the PTV volume expressed in cm 3 . Body-PTV healthy tissue V 10% , V 20% , V 105% and V 107% were defined as surrogates for extra-targettissue irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were selected based on their anatomy (large or pendulous breasts, CT simulation breast volume .1000 cm 3 or when breast tissue tended to fall towards the mid axillary line, and/or a BMI of .25 kg m 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations